If it's not what You are looking for type in the equation solver your own equation and let us solve it.
101=n+3(6n+2)
We move all terms to the left:
101-(n+3(6n+2))=0
We calculate terms in parentheses: -(n+3(6n+2)), so:We get rid of parentheses
n+3(6n+2)
We multiply parentheses
n+18n+6
We add all the numbers together, and all the variables
19n+6
Back to the equation:
-(19n+6)
-19n-6+101=0
We add all the numbers together, and all the variables
-19n+95=0
We move all terms containing n to the left, all other terms to the right
-19n=-95
n=-95/-19
n=+5
| 4n^2+20n=24 | | 6b-24=8b-18 | | 101=n+3(6n+2 | | x^2-1=6x-6 | | 3(-4n+1)=75 | | 4u-9=47 | | 90-0.40x=60+0.70x | | 8=m–3 | | 1.1x-3.2=0.5x-2.06 | | 6=2y=2 | | 2(6+4r)+3=63 | | X*y=6+y | | 6-3d=-5(4+d)+2d | | 2x8= | | ,2•8v=54+v | | 30x=x+20 | | 50=5w+15 | | d+1/2=-9(1/4) | | 7(3w-2)=w+ | | (2x/x-1)-2=0.05 | | 5(b+4)=-20 | | 2/3x-1=-15 | | y^-2=36/49 | | -96=5r+4(5r+1) | | 2m+3=m+3 | | 5p-4(p-4)=11(3p-8) | | 3p^2-3p-21=7+2p^2 | | x/x=7200.6 | | (6+6i)-(2+i)=0 | | 4(m-5)=6m+4 | | 12x^2+66x-240=0 | | 1/6x-4=22 |